Fetal-Derived Immune Cells at the Roots of Lifelong Pathophysiology - Mass, Elvira; Gentek, Rebecca (Frontiers in Cell and Developmental Biology, 2021)
Tissue-resident innate immune cells exert a wide range of functions in both adult homeostasis and pathology. Our understanding of when and how these cellular networks are established has dramatically changed with the recognition that many lineages originate at least in part from fetal sources and self-maintain independently from hematopoietic stem cells. Indeed, fetal-derived immune cells are found in most organs and serous cavities of our body, where they reside throughout the entire lifespan. At the same time, there is a growing appreciation that pathologies manifesting in adulthood may be caused by adverse early life events, a concept known as “developmental origins of health and disease” (DOHaD). Yet, whether fetal-derived immune cells are mechanistically involved in DOHaD remains elusive. In this review, we summarize our knowledge of fetal hematopoiesis and its contribution to adult immune compartments, which results in a “layered immune system.” Based on their ontogeny, we argue that fetal-derived immune cells are prime transmitters of long-term consequences of prenatal adversities. In addition to increasing disease susceptibility, these may also directly cause inflammatory, degenerative, and metabolic disorders. We explore this notion for cells generated from erythro-myeloid progenitors (EMP) produced in the extra-embryonic yolk sac. Focusing on macrophages and mast cells, we present emerging evidence implicating them in lifelong disease by either somatic mutations or developmental programming events resulting from maternal and early environmental perturbations.